Validation of a field test for the non-invasive determination of badminton specific aerobic performance - Wonisch, M.; Hofmann, P.; Schwaberger, G.; von Duvillard, S. P.; Klein, W. (British Journal of Sports Medicine, 2003)
Aim: To develop a badminton specific test to determine on court aerobic and anaerobic performance.